PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) TERHADAP KINERJA BANK PADA MASA SEBELUM DAN SELAMA PANDEMI COVID-19 - Verina, Dhea Chandra; Rohman, Abdul (Diponegoro Journal of Accounting, 2024)
This research aims to examine the effect of environmental, social, and governance disclosure on bank performance before and during the covid-19 pandemic period and to test the differences of ESG disclosure before and during the covid-19 pandemic period. This research uses environmental, social, and governance disclosure as independent variable and bank performance represented by ROA as the dependent variable. The population used in this research are banking sector companies that listed on the Indonesia Stock Exchange in 2017-2019 for regression model 1 and 2020-2022 for regression model 2. Using the purposive sampling method, 36 research samples were used in regression model 1 and 2. The statistical technique used in this research is panel data regression analysis and paired sample t-test analysis with E-views 13 to test the hypotheses. The results of this research show that environmental disclosure has an insignificant positive effect on ROA before the covid-19 pandemic period and has a significant positive effect during the covid-19 pandemic period, social disclosure has an insignificant positive effect on ROA before the covid-19 pandemic period and has an insignificant negative effect during the covid-19 pandemic period, governance disclosure has a significant negative effect before the covid-19 pandemic period and has an insignificant positive effect during the covid-19 pandemic period. This research also finds that there is a significant difference between ESG disclosure before and during the covid-19 pandemic period.